Language of Instruction Policy in Science Programs: Science University Students’ Voices - Alhamami, M. (Jurnal Pendidikan IPA Indonesia, 2019)
The language of instruction policy in science university programs is chosen by different stakeholders. The voice of science university students (SUSs) has been neglected in many science programs around the world. A review of the literature shows that among all stakeholders, SUSs are influenced mostÃ¢â‚¬â€both positively and negativelyÃ¢â‚¬â€by the medium of instruction policy. This study analyzed the perspectives of 186 SUSs regarding the use of the countryÃ¢â‚¬â„¢s official language as the medium of instruction (OLMI) and a foreign language as the medium of instruction (FLMI) in science undergraduate programs. The results showed that the majority of the participants were negatively affected by the policy of using FLMI and that their voices have been neglected. Most of the SUSs supported changing the policy to OLMI. Thus, there were contradictions between the objectives of the current policy and its real outcomes. The policy reduced the achievement of learning outcomes in science programs. The study recommended an in-depth investigation of the outcomes of the medium of instruction policy among SUSs. Neglecting the voice of science students hindered their learning outcomes.